Sustainable learning and education: A curriculum for the future - Hays, Jay; Reinders, Hayo (International Review of Education, 2020)
This article introduces sustainable learning and education (SLE), an emerging philosophy of learning and teaching founded on principles of sustainability. SLE is not necessarily education for sustainability, but rather sustainable learning, a new and different idea. The intention behind SLE is to create and proliferate sustainable curricula and methods of learning and teaching. These are designed to instil in people the skills and dispositions to thrive in complicated, challenging and ever-changing circumstances, and contribute to making the world a better place. This article contributes to the literature by (1) elucidating the concept and purpose of SLE; (2) enumerating principles of sustainability that apply in the educational and professional development context; and (3) proposing a curriculum for SLE framed as a university course or professional development programme. The authors emphasise the importance of systems and ecological thinking and the essential role of self-sufficiency as both a means and an end of sustainable learning and education. They conclude with a comment on community: the more fully we accept and appreciate our neighbours, organisations and societies as important, interdependent and deserving of a viable future, and the more we engage with them towards positive ends, the more universally accepted the imperative of sustainability will be, and the more likely we are to attain it.